High Level Modeling and Hardware Implementation of Image Processing Algorithms Using XSG - Kamel Messaoudi; Hakim Doghmane; Hocine Bourouba; El-Bay Bourennane; Salah Toumi (Springer, 2019)
Design of Systems-on-Chip has become very common especially with the remarkable advances in the field of high-level system modeling. In recent years, Matlab also offers a Simulink interface for the design of hardware systems. From a high-level specification, Matlab provides self-generation of HDL codes and/or FPGA configuration codes while providing other benefits of easy simulation. In addition, a large part of the Systems-on-Chip use at least one image processing algorithm and at the same time border detection is one of the most used algorithms. This paper presents a study and a hardware implementation of various algorithms of borders detection realized under Xilinx System-Generator. The various algorithms are implemented using Xilinx FPGA device, the simulation and synthesis results are also compared. We use the Xilinx Zed-Board for physical implementations in-the-loop.
Lecture Notes in Electrical Engineering 682